Temperament, poczucie własnej skuteczności i jakość życia kobiet regularnie uprawiających sport w porównaniu z kobietami nieaktywnymi fizycznie = Temperament, self-efficacy and quality of life of women regularly doing sport in comparison with physically inactive women - Grześkowiak, Barbara; Siwy-Hudowska, Anna (Journal of Education, Health and Sport, 2016)
Grześkowiak Barbara, Siwy-Hudowska Anna. Temperament, poczucie własnej skuteczności i jakość życia kobiet regularnie uprawiających sport w porównaniu z kobietami nieaktywnymi fizycznie = Temperament, self-efficacy and quality of life of women regularly doing sport in comparison with physically inactive women. Journal of Education, Health and Sport. 2016;6(6):359-374. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55761 http://ojs.ukw.edu.pl/index.php/johs/article/view/3587 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Temperament, poczucie własnej skuteczności i jakość życia kobiet regularnie uprawiających sport w porównaniu z kobietami nieaktywnymi fizycznie Temperament, self-efficacy and quality of life of women regularly doing sport in comparison with physically inactive women Barbara Grześkowiak, Anna Siwy-Hudowska SWPS Uniwersytet Humanistycznospołeczny w Warszawie, Wydział Psychologii University of Social Sciences and Humanities in Warsaw, Psychology Department Streszczenie Wprowadzenie i cel pracy Celem pracy było zbadanie różnic w subiektywnej ocenie jakości życia i jej sfer oraz w zakresie cech temperamentu i poczucia własnej skuteczności pomiędzy kobietami regularnie uprawiającymi sport a kobietami deklarującymi brak aktywności sportowej, a także sprawdzenie, jakie jest znaczenie temperamentu i poczucia własnej skuteczności dla jakości życia kobiet w porównywanych grupach. Materiał i metoda Badanie było przeprowadzane w dwóch grupach kobiet: 35 uprawiających sport i 35 nieaktywnych fizycznie (brak jakiegokolwiek zaangażowania w uprawianie sportu). Osoby wypełniły kwestionariusze samoopisowe: Kwestionariusz Jakości Życia, Kwestionariusz Temperamentu EAS, Skalę Uogólnionej Własnej Skuteczności (GSES) oraz ankietę dotyczącą danych demograficznych i sportowych. Wyniki Kobiety uprawiające sport miały wyższe poczucie własnej skuteczności oraz wyżej oceniły wszystkie sfery własnej jakości życia niż kobiety nieaktywne sportowo. Ponad 57% kobiet nie uczestniczących w regularnych zajęciach sportowych chciałaby poprawić swoją kondycję fizyczną. Wykazano także, że aktywność fizyczna poprzez podnoszenie poczucia własnej skuteczności może mieć pozytywny wpływ na subiektywną ocenę jakości życia. W zakresie cech temperamentu kobiety aktywne fizycznie charakteryzowały się istotnie niższym niezadowoleniem niż kobiety nieaktywne fizycznie. Wraz ze spadkiem niezadowolenia przy występowaniu aktywności fizycznej zwiększa się jakość życia badanych kobiet. Wnioski Uprawianie sportu sprzyja doświadczaniu pozytywnych zmian w sobie. Może to skutkować podniesieniem poczucia własnej skuteczności, co pozwala lepiej myśleć o sobie i efektywniej uzyskiwać cele, które są ważne dla jakości życia jednostki. Słowa kluczowe: jakość życia, temperament, poczucie własnej skuteczności, aktywność fizyczna. Abstract Introduction and purpose The aim of the work was to analyse the differences in subjective quality of life and its domains and, moreover, in the field of temperamental traits and self-efficacy between the women regularly doing sport in comparison to those who do not. The impact of temperament and self-efficacy on the quality of life was also verified. Material and method The research was carried out on two groups of females: 35 active and 35 physically inactive (doing no sports whatsoever). Participants completed self-description questionnaires: Quality of Life Questionnaire, EAS Temperament Questionnaire, SES Self-Efficacy Scale and the form of demographic and sport details. Results Active women had higher self-efficacy and better assessed each of domains of the quality of life than inactive women. More than 57% of inactive women wanted to improve their physical condition. It was shown also that physical activity through self-efficacy improvement can positively influence subjective quality of life. In the field of temperamental traits, active women were characterized by significantly lower emotionality-distress than inactive women. When emotionality-distress decreased with the presence of physical activity, the person's quality of life increased. Conclusions Doing sport is conductive to experiencing of positive changes in one's life. This may result in higher self-efficacy which allows women to think better about themselves and more effectively reach goals that are important for the quality of life. Keywords: quality of life, temperament, self-efficacy, physical activity, sport.